3D bio-printed endometrial construct restores the full-thickness morphology and fertility of injured uterine endometrium. (February 2023) - Nie, Nanfang; Gong, Lin; Jiang, Deming; Liu, Yanshan; Zhang, Jingwei; Xu, Jiaqi; Yao, Xudong; Wu, Bingbing; Li, Yu; Zou, Xiaohui
Abstract: Severe damage to the uterine endometrium, which results in scar formation and endometrial dysfunction, eventually leads to infertility or pregnancy-related complications. No effective therapeutic treatment is currently available for such injuries owing to the structural complexity, internal environment, and function of the uterus. Three-dimensional (3D) bio-printing to engineer biomimetic structural constructs provides a unique opportunity for tissue regeneration. Herein, using 3D extrusion-based bioprinting (EBB), we constructed a bilayer endometrial construct (EC) based on a sodium alginate-hyaluronic acid (Alg-HA) hydrogel for functional regeneration of the endometrium. The upper layer of the 3D bio-printed EC is a monolayer of endometrial epithelial cells (EECs), while the lower layer has a grid-like microstructure loaded with endometrial stromal cells (ESCs). In a partial full-thickness uterine excision rat model, our bilayer EC not only restored the morphology and structure of the endometrial wall (including organized luminal/ glandular epithelium, stroma, vasculature and the smooth muscle layer), but also significantly improved the reproductive outcome in the surgical area after implantation (75%, 12/16, p <  0.01). Therefore, repair of the uterine endometrium using the developed 3D bio-printed bilayer EC may represent an effective regenerative treatment for severe endometrial injury. Statement of significance: Achieving structural and functional recovery of the endometrium following severe injury is still a challenge. Here, we designed a 3D bio-printed endometrial construct (EC) to mimic the native bilayer structure and cellular components of the endometrium. The bio-printed EC consists of a dense upper layer with endometrial epithelial cells and a lower layer with endometrial stromal cells. In particular, the 3D bio-printed EC significantly improved the reproductive outcome in the surgical area (75%, 12/16) compared to that of the cell-loaded non-printed group (12.5%, 2/16). This study demonstrates that a biomimetic bilayer construct can facilitate endometrial repair and regeneration. Therefore, an endometrial cells-loaded 3D-bioprinted EC is a promising therapeutic option for patients suffering from severe endometrial damage. Graphical abstract: Image, graphical abstract